Identification of the shared gene signatures and molecular mechanisms between multiple sclerosis and non-small cell lung cancer - Yang, Jingyun; Hu, Xiaofei; Wang, Yu; Liu, Wenying; Zhang, Mengjie; Zhang, Anmei; Ni, Bing (Frontiers in Immunology, 2023)
The association between Multiple Sclerosis (MS) and Non-Small Cell Lung Cancer (NSCLC) has been the subject of investigation in clinical cohorts, yet the molecular mechanisms underpinning this relationship remain incompletely understood. To address this, our study aimed to identify shared genetic features, shared local immune microenvironments, and molecular pathways between MS and NSCLC. To achieve this goal, we selected multiple Gene Expression Omnibus (GEO) datasets, including GSE19188, GSE214334, GSE199460, and GSE148071, to obtain gene expression levels and clinical information from patients or mouse with MS and NSCLC. We employed Weighted Gene Co-expression Network Analysis (WGCNA) to investigate co-expression networks linked to MS and NSCLC, and used scRNA-seq analysis to explore the local immune microenvironment of MS and NSCLC and identify possible shared components. Our analysis identified the most significant shared gene in MS and NSCLC, Phosphodiesterase 4A (PDE4A), and we analyzed its expression in NSCLC patients and its impact on patient prognosis, as well as its molecular mechanism. Our results demonstrated that high expression of PDE4A was associated with poor prognosis in NSCLC patients, and Gene Set Enrichment Analysis (GSEA) revealed that PDE4A is involved in immune-related pathways and has a significant regulatory effect on human immune responses. We further observed that PDE4A was closely linked to the sensitivity of several chemotherapy drugs. Given the dearth of studies investigating the molecular mechanisms underlying the correlation between MS and NSCLC, our findings suggest that there are shared pathogenic processes and molecular mechanisms between these two diseases, and that PDE4A represents a potential therapeutic target and immune-related biomarker for patients with both MS and NSCLC.